Performance of Diaphragm Walls during Ultra-Deep Excavations in Karst Areas: Field Monitoring Analysis - Xingzhong Nong; Yanhong Wang; Benhai Lin; Wentian Xu; Wuzhang Luo; Ren Tang (Advances in Civil Engineering)
Deep foundation pit excavations have become more extensive for the construction of underground spaces with rapid urbanization. Diaphragm walls are commonly used to support deep excavations. However, due to the complex geological conditions in karst areas, construction accidents frequently occur during the excavation of foundation pits. This study aims to investigate the performance of diaphragm walls in karst areas through field monitoring analysis. A kick-in deformation mode of the diaphragm wall is revealed during the foundation pit excavation. Furthermore, the results show that the diaphragm walls present multiple deformation modes rather than a single mode. Additionally, this study proposes a method to calculate the lateral displacement of the diaphragm walls at different depths. It is found that the karst caves have a considerable impact on the stability of diaphragm walls, as demonstrated by their lateral displacement. The hidden karst caves reduce the bearing capacity of the bedrock, rendering it insufficient to resist the active earth pressure. As a result, the bottom of the diaphragm wall is kicked into the foundation pit, causing significant lateral displacement and posing risks during excavation. The findings of this study contribute to the design and construction of similar excavations in karst areas.